2019
DOI: 10.1093/jjco/hyz122
|View full text |Cite
|
Sign up to set email alerts
|

Wedge resection versus segmentectomy in patients with stage I non–small-cell lung cancer unfit for lobectomy

Abstract: Objective The present study aimed to compare the outcomes of wedge resection and segmentectomy in patients with clinical stage I non–small-cell lung cancer (NSCLC) who were unfit for lobectomy. Methods Between April 2007 and December 2015, 99 patients with stage I NSCLC who were considered unfit for lobectomy and had undergone sublobar resection were identified. Propensity scores were estimated for multivariable analyses, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…A retrospective study indicated that sub-lobar resection might achieve similar survival rates to lobectomy in elderly stage I NSCLC patients (10). A result was observed in that segmentectomy failed to show superiority in terms of survival compared with wedge resection for patients with stage I NSCLC (11). Thus, the optimal extent of resection for elderly patients with stage IA disease remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study indicated that sub-lobar resection might achieve similar survival rates to lobectomy in elderly stage I NSCLC patients (10). A result was observed in that segmentectomy failed to show superiority in terms of survival compared with wedge resection for patients with stage I NSCLC (11). Thus, the optimal extent of resection for elderly patients with stage IA disease remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who cannot tolerate radical surgery are frequently older patients with comorbidities or impaired pulmonary function. Several studies have reported that segmentectomy and wedge resection show similar survival rates for patients who are unfit for lobectomy ( 6 9 ). Additionally, although wedge resection is a non-anatomical resection, it may be optimal for patients who cannot undergo lobectomy.…”
Section: Introductionmentioning
confidence: 99%
“…15 It is reported that oncological results similar to lobectomy were obtained with segmentectomy for the surgical treatment of early stage non-small cell lung cancer. [1][2][3]6,7,11 Segmentectomy may be an alternative to lobectomy in non-small cell lung cancers, even for the medical condition of the patient who is suitable for lobectomy, 7,8 or segmentectomy may be an alternative to lobectomy in selected patients. 1,3,19,20 In a study by Yamato et al, 21 on histopathological subtype lung adenocarcinoma as in our study, 5-year survival was 87.5% in the segmentectomy group and 85.5% in the lobectomy group.…”
Section: Discussionmentioning
confidence: 99%
“…5 In parallel with developments in radiological imaging methods, increase in detection of small-sized lung tumors, especially adenocarcinoma histopathological type, 6 interest has increased in sublobar resections. 1,[7][8][9] Therefore, the role of segmentectomy in the surgical treatment of early non-small cell lung cancer has become controversial.…”
Section: Introductionmentioning
confidence: 99%